2009
DOI: 10.4025/cienccuidsaude.v7i4.6626
|View full text |Cite
|
Sign up to set email alerts
|

Dor em recém-nascidos: a percepção da equipe de saúde

Abstract: RESUMO Trata-se de um estudo descritivo, de natureza qualitativa, desenvolvida com os objetivos de conhecer a percepção da equipe de saúde sobre a dor em recém-nascidos, a forma como a mesma é reconhecida e as medidas tomadas para amenizá-la. Os dados foram coletados no período março a maio de 2005, junto a 36 profissionais de saúde que prestam assistência direta aos recém-nascidos nas unidades de terapia intensiva e semi-intensiva neonatal de um hospital escola da cidade de Maringá-PR. Os resultados, estão ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…During this period, the environment for mothers and children must be as comfortable as possible.. 11 As stated by Correa and Neves, the prevention, assessment and treatment of neonatal pain are top priorities. It is important to find a solution that allows everyone to work, do a good job, produce better working solutions and define what is needed.. 12 In the studies by Alencar and Ramos, the authors aimed to characterize the assessment of pain in NBs who were hospitalized in the NICU, proposing to demonstrate the importance of properly assessing pain and treating it efficiently..Therefore, the authors determined that scientific evidence demonstrated that in addition to some discomfort caused by a large amount of sensory stimulation in the intensive care unit environment, the NB admitted to the intensive care unit received a procedure that would cause pain, so the use of the pain assessment scale is crucial, so that the newborn can be hospitalized in a more harmonious and humane way. Therefore, it is necessary to adequately prepare the professionals who work in these sectors, and to be attentive to all signs that may indicate that the patient is in a certain state of pain, so that the mechanism mentioned in this study can be used for pain relief, and thus, provide for those who already suffer, newborns bring greater comfort.…”
Section: Indicatormentioning
confidence: 99%
“…During this period, the environment for mothers and children must be as comfortable as possible.. 11 As stated by Correa and Neves, the prevention, assessment and treatment of neonatal pain are top priorities. It is important to find a solution that allows everyone to work, do a good job, produce better working solutions and define what is needed.. 12 In the studies by Alencar and Ramos, the authors aimed to characterize the assessment of pain in NBs who were hospitalized in the NICU, proposing to demonstrate the importance of properly assessing pain and treating it efficiently..Therefore, the authors determined that scientific evidence demonstrated that in addition to some discomfort caused by a large amount of sensory stimulation in the intensive care unit environment, the NB admitted to the intensive care unit received a procedure that would cause pain, so the use of the pain assessment scale is crucial, so that the newborn can be hospitalized in a more harmonious and humane way. Therefore, it is necessary to adequately prepare the professionals who work in these sectors, and to be attentive to all signs that may indicate that the patient is in a certain state of pain, so that the mechanism mentioned in this study can be used for pain relief, and thus, provide for those who already suffer, newborns bring greater comfort.…”
Section: Indicatormentioning
confidence: 99%